Boesenbergia rotunda and Its Pinostrobin for Atopic Dermatitis: Dual 5-Lipoxygenase and Cyclooxygenase-2 Inhibitor and Its Mechanistic Study through Steady-State Kinetics and Molecular Modeling - Desy Liana; Chatchakorn Eurtivong; Anuchit Phanumartwiwath (MDPI AG, 2024)
Human 5-lipoxygenase (5-LOX) and cyclooxygenase-2 (COX-2) are potential targets for suppressing pruritic skin inflammation in atopic dermatitis (AD). In addition, Staphylococcus aureus colonization and oxidative stress worsen AD skin conditions. We aimed to investigate anti-inflammatory activity, using 5-LOX and COX-2 inhibitions, and the anti-staphylococcal, and antioxidant potentials of several medicinal plants bio-prospected from traditional medicine related to AD pathogenesis. Essential oils and hexane fractions were prepared and analyzed using gas chromatography-mass spectrometry. Boesenbergia rotunda hexane extract displayed anti-Staphylococcus aureus (MIC = 10 µg/mL) and antioxidant activities (IC50 = 557.97 and 2651.67 µg/mL against DPPH and NO radicals, respectively). A major flavonoid, pinostrobin, was further nonchromatographically isolated. Pinostrobin was shown to be a potent 5-LOX inhibitor (IC50 = 0.499 µM) compared to nordihydroguaiaretic acid (NDGA; IC50 = 5.020 µM) and betamethasone dipropionate (BD; IC50 = 2.077 µM) as the first-line of AD treatment. Additionally, pinostrobin inhibited COX-2 (IC50 = 285.67 µM), which was as effective as diclofenac sodium (IC50 = 290.35 µM) and BD (IC50 = 240.09 µM). This kinetic study and molecular modeling showed the mixed-type inhibition of NDGA and pinostrobin against 5-LOX. This study suggests that B. rotunda and its bioactive pinostrobin have promising properties for AD therapy.